Potential Differences in Clinical Features, Disease Activity, Function and Impact of Disease Between Oligo and Polyarticular Psoriatic Arthritis. Issue 1 (January 2021) - Lubrano, Ennio; Scriffignano, Silvia; Fatica, Mauro; Perrotta, Fabio Massimo
Objective: The primary aim of the study was to assess the potential differences in clinical features, disease activity, function and impact of disease between Psoriatic Arthritis (PsA) patients with oligoarticular and polyarticular involvement. Methods: Consecutive PsA patients attending our unit were divided into 2 groups: 1) Oligoarticular (<5 involved joints with or without enthesitic/axial manifestations) and 2) Polyarticular (≥5 joints with or without enthesitic/axial manifestations). A full clinical examination with the assessment of disease characteristics, disease activity (DAPSA, MDA), function (HAQ-DI) and impact of disease (PsAID-12) was performed. Furthermore, a 6-month follow-up evaluation was carried out in order to assess disease differences at baseline and at follow-up. Results: Of the 102 enrolled patients, oligoarticular subset was present in 63 (61.7%), while 39 (38.3%) patients had polyarticular involvement. Patients with oligoarticular subset showed, at baseline evaluation, lower values of global disease activity assessed by physician, HAQ-DI and DAPSA compared to patients with polyarticular pattern. No differences in the impact of disease (PsAID), patient global assessment of disease activity or pain were found. At 6-month follow-up, no significant changes in each group occurred. Conclusion: Our study showed some differences in patients with oligoarticular and polyarticular involvement in terms of disease activity and HAQ-DI, while the overall impact of the disease and the presence of enthesitis, dactylitis and axial disease seem to be similar, with no substantial changes after 6-month follow-up. These results could mean that clinical phenotype might not be responsible for the impact of the disease perceived by the patient.